Public Encounters and Government Chatbots: When Servers Talk to Citizens. - Alishani, Art; Homburg, Vincent; Velsberg, Ott (Public Administration Review)
Public service providers around the world are now offering chatbots to answer citizens' questions and deliver digital services. Using these artificial intelligence‐powered technologies, citizens can engage in conversations with governments through systems that mimic face‐to‐face interactions and adjust their use of natural language to citizens' communication styles. This paper examines emerging experiences with chatbots in government interactions, with a focus on exploring what public administration practitioners and scholars should expect from chatbots in public encounters. Furthermore, it seeks to identify what gaps exist in the general understanding of digital public encounters.